2020
DOI: 10.1108/md-09-2019-1268
|View full text |Cite
|
Sign up to set email alerts
|

An MCDA cause-effect factors model for the implementation of Greenstone Digital Library software

Abstract: PurposeThe selection of effective library software not only plays an important role for students, academic staff and the library staff but also helps an institution by having the library management system more centralized. Therefore, the aim of this study is to develop a multiple-criteria decision analysis (MCDA) cause and effect factor model for the implementation of the Greenstone Digital Library (GSDL) software.Design/methodology/approachA thorough review of the literature is conducted to develop an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 66 publications
(109 reference statements)
0
12
0
Order By: Relevance
“…This has eventually evolved into a situation where the accuracy of people's access to the information they need is decreasing with the growth of information resources. As a result, users expect libraries to provide more personalized services to improve the utilization of information resources [17]. First, users want to have mobile access to resources.…”
Section: Related Workmentioning
confidence: 99%
“…This has eventually evolved into a situation where the accuracy of people's access to the information they need is decreasing with the growth of information resources. As a result, users expect libraries to provide more personalized services to improve the utilization of information resources [17]. First, users want to have mobile access to resources.…”
Section: Related Workmentioning
confidence: 99%
“…Under the multimedia network technology, the establishment of the personalized information service system of the smart library is the basis to ensure better service of resources. It can truly provide resources according to users' needs and enable users to obtain the richest resources, if allowed [ 14 , 15 ]. The hardware function of the designed intelligent library personalized information service system is to use the client to feed back the data resources that customers need to retrieve and use the data collector module to collect library resources, and the data integrator will integrate and process the collected resources.…”
Section: Personalized Information Service System Of Smart Library Und...mentioning
confidence: 99%
“…4 Rathee carried out a study and reported through a paper entitled "Develop a multiple-criteria decision analysis (MCDA) cause and effect factor model for the implementation of the Greenstone Digital Library (GSDL) software" (Rathee et al, 2020). 5 DEMATEL, a MCDM technique helps the managers to improve the status of the effect group and its performance because they can easily do this by improving the cause group's criteria (Kaushik and Somvir 2015). 6 A few LIS distributions have given some presentation or outline of the Delphi technique in LIS research; notwithstanding, these distributions each have a few constraints.…”
Section: Literature Reviewmentioning
confidence: 99%